Optimal code length for bursty sources with deadlines - Javidi, T.; Swamy, R.N. (2009 IEEE International Symposium on Information Theory, 2009)
Data transmission over a discrete memoryless channel is considered when the arrival of data is bursty and is subject to a delay deadline. An exponential decay of the probability of delay violation with respect to a large delay deadline is proved when the block length scales linearly with the deadline. When considered in conjunction with Gallager's error exponents, the first natural consequence of this result is a separation principle: a separated scheme of buffering traffic and block-coding transmissions achieves arbitrarily high reliability for an asymptotically large delay budget. Furthermore, the exponential decay nature of the result provides some insight as how to budget the delay limit between the coding time and the waiting time in the queue.